Kyrgyz Republic Economic Update, Spring 2016 : Policy Challenges in a Difficult Environment - World Bank Group (World Bank, Washington, DC, 2016)
The Kyrgyz economy has remained resilient in the face of continued significant external head winds in 2015, but sources of vulnerability have increased.While overall Gross Domestic Product (GDP)growth is estimated to have slowed to 3.5 percent in 2015, this deceleration was mostly on accountof lower gold production. Non-gold output growth remained robust at 4.5 percent (essentiallyunchanged from 2014), although with significant shifts in drivers. The policy stance was broadly appropriate.Looking forward to 2016 and beyond, economic activity is expected to slow down,with significant downside risks.With gold production expected to decline in coming years, andagricultural output growth returning to historical averages, overall growth is projected to moderate to 3.4 percent and 3.1 percent in 2016 and 2017 respectively. For public policy, the main challenge will be to reconcile the objective of supporting economic activity with principles of prudent management.Indeed, while the Kyrgyz Republic’s debt path remains sustainable, there are good reasons to be concerned over risks of debt distress. The Special Focus section of this Economic Update analyzes the features of the Kyrgyz Republic’s public debt and explains the factors behindthe recent deterioration of the debt sustainability outlook. It concludes by pointing out some of the policy steps that ought to be taken in response.